Sistem Digital Manajemen Aset Berbasis Web - Vikhry Huki Alvianto; Poltak Pancarian Situmorang (UNIVERSITAS KALBIS, 2022)
The use of technology in a company can help in carrying out existing business processes. One of the problems in the company is in carrying out asset management, the information is incomplete because the recording is still manual. In this study, we made a web-based asset management system using the waterfall method which consists of 6 stages. The first is system analysis, at this stage an analysis is carried out in the form of problem identification to be able to adjust to the needs of the system to be made. The second stage is system design using UML (Unified Modeling Language) so that the flow in making the system is clearer. The third stage of system development using Microsoft Visual Studio and Microsoft SQL Server as the database. The fourth stage is testing the system. The fifth stage is the implementation stage of the system and the last stage is maintenance to perform maintenance on the system. The result of this research is a website that manage the asset.